2013
DOI: 10.1186/1472-6963-13-233
|View full text |Cite
|
Sign up to set email alerts
|

Assessing participation in a community-based health planning and services programme in Ghana

Abstract: BackgroundCommunity participation is increasingly seen as a pre-requisite for successful health service uptake. It is notoriously difficult to assess participation and little has been done to advance tools for the assessment of community participation. In this paper we illustrate an approach that combines a ‘social psychology of participation’ (theory) with ‘spider-grams’ (method) to assess participation and apply it to a Community-based Health Planning and Services (CHPS) programme in rural Ghana.MethodsWe dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(147 citation statements)
references
References 35 publications
3
142
0
2
Order By: Relevance
“…However, there was no clear mechanism established for ensuring that committee members collect views and ideas from the community members about their health needs. A qualitative study in Ghana (Baatiema, Skovdal, Rifkin, & Campbell, 2013) reported that the community per se did not participate directly in identifying their health needs; instead, a few people, particularly experts, were the key people in designing various health programmes on the behalf of the community.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no clear mechanism established for ensuring that committee members collect views and ideas from the community members about their health needs. A qualitative study in Ghana (Baatiema, Skovdal, Rifkin, & Campbell, 2013) reported that the community per se did not participate directly in identifying their health needs; instead, a few people, particularly experts, were the key people in designing various health programmes on the behalf of the community.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many potential impediments to effective community engagement. These include competing interests and goals of different community factions, lack of continuous commitment to engagement (5), lack of recognition that local knowledge can constitute expert knowledge that should contribute to health policy decisions (11), and top-down hierarchical community management structures (5,11). In the interests of health equity, it is imperative that the most vulnerable community members are part of the decision-making process.…”
Section: Comprehensive Primary Health Carementioning
confidence: 99%
“…More recently, the message that community involvement is crucial to health service delivery (11) has been renewed in a special edition of the Lancet that commemorates the thirtieth anniversary of the Declaration (58) as well as in a WHO report on the social determinants of health and health equity (26), both published in 2008. Health systems that adopt primary health care approaches experience better overall population health (86,87), fewer health inequalities (24,87), lower health care expenditures (36,59,84), and enhanced quality of care (12).…”
Section: Comprehensive Primary Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…The utility of these indicators in determining the status of community participation in community-based health programs has been demonstrated in other studies [17][18][19][20][21] . After the ACPP, approximately 85% of the residents in the ACPP village participated in malaria control, suggesting that the intervention was effective in mobilizing community participation.…”
Section: Discussionmentioning
confidence: 99%